Cultural dynamics influencing decision-making during the COVID-19 pandemic: the Italian case - Costa, Sara; Carrus, Giuseppe (Frontiers in Psychology, 2024)
The COVID-19 pandemic has brought about significant changes to the life of most individuals, worldwide. This study explores the cultural factors influencing decision-making during the pandemic, and is part of the CORNER Project, funded by the Research Council of Norway, aimed at understanding institutional response in the early phases of the Covid-19 emergency in Norway, Sweden, and Italy. Semi-structured interviews with key political-administrative leaders in Italy (N = 35) were conducted and content-analyzed, allowing the identification of the underlying cultural dynamics that played a role in these decisions. Thematic analysis was used to assess the influence of cultural factors on the crisis management and early reaction of institutions and citizens to the spread of Covid. In line with previous studies, and as expected, the individualism vs. collectivism dimension can explain differential health outcomes during the outbreak. In this paper we argue that individualism–collectivism cultural values can also play a pivotal role in public compliance with Covid-19 restrictions, and psychological responses during the pandemic.